PENGARUH PERSEPSI KEADILAN TERHADAP KEPATUHAN WAJIB PAJAK DENGAN KEPERCAYAAN SEBAGAI VARIABEL MEDIASI (STUDI PADA WPOP DI KOTA MAKASSAR) - Radia; Amril; Ridwan, Mukminati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effect of perceived fairness on taxpayer compliance with trust as a mediating variable. This research employs a quantitative approach with a causal associative research design. The population consists of individual taxpayers registered at the West Makassar Primary Tax Office (KPP Pratama Makassar Barat) with a total of 999 active taxpayers in 2026. Purposive sampling was employed, resulting in 100 respondents. Data were collected through questionnaires and analyzed using multiple linear regression and the Sobel test with SPSS version 26. The results show that perceived fairness and trust have a positive and significant effect on taxpayer compliance, with t-values of 4.588 and 6.126, respectively, exceeding the t-table value of 1.984 (sig. 0.000 < 0.05). The Sobel test results indicate that trust mediates the effect of perceived fairness on taxpayer compliance, with a Sobel test statistic of 3.49 > 1.69 at the 5% significance level. These findings demonstrate that higher perceived fairness and stronger trust in the government lead to increased taxpayer compliance.